Uncommon Diseases in the ICU - Leone, Marc; Martin, Claude; Vincent, Jean-Louis (Springer International Publishing : Imprint: Springer, 2014)
This book highlights the practical characteristics of uncommon diseases and presents the most relevant features for the management of intensive care units. It does not aim to provide an exhaustive description of uncommon diseases, focusing instead on the major diseases that intensivists may encounter in their clinical practice. After a brief introduction on the epidemiology and pathophysiology of each disease, the authors emphasize the aspects related to diagnosis and treatment, providing concise and pragmatic guidance for residents and intensivists who care for patients with uncommon diseases. Although by definition uncommon diseases have a low prevalence in the general population, they can affect a large number of patients admitted to intensive care units, as they can often be diagnosed at intensive care units. Indeed, often a complication of the disease is what leads to the patient's being admitted to an intensive care unit.